2020
DOI: 10.21873/invivo.12094
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Seizures in Patients With 1-3 Cerebral Metastases Receiving Local Therapies Plus Whole-brain Radiotherapy

Abstract: Background/Aim: Seizures impair patients' quality of life. The prognostic role of pre-treatment seizures in patients with 1-3 cerebral metastases receiving local therapies plus whole-brain radiotherapy (WBRT) was investigated. Patients and Methods: In 249 patients, prevalence, risk factors and associations of pre-treatment seizures with survival were retrospectively evaluated. Age, gender, performance score, tumor type, number of lesions, extra-cerebral metastases, and time from tumor diagnosis to treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Some demographic aspects have been scarcely analyzed in previous studies, and there is no clear consensus on the results obtained. Thus, while Puri et al (2020) [36] et al reported that age is the only variable that correlates negatively with the occurrence of pre-and postoperative seizures, other authors such as Witteler et al (2020) [37] and Maschio et al (2022) [38] did not observe any significant correlation between age and seizure risk. In our study, no statistically significant differences were found with respect to either sex (p = 0.061) or age (p = 0.753).…”
Section: Discussionmentioning
confidence: 91%
“…Some demographic aspects have been scarcely analyzed in previous studies, and there is no clear consensus on the results obtained. Thus, while Puri et al (2020) [36] et al reported that age is the only variable that correlates negatively with the occurrence of pre-and postoperative seizures, other authors such as Witteler et al (2020) [37] and Maschio et al (2022) [38] did not observe any significant correlation between age and seizure risk. In our study, no statistically significant differences were found with respect to either sex (p = 0.061) or age (p = 0.753).…”
Section: Discussionmentioning
confidence: 91%